Effect of bicarbonate and phosphate on arsenic release from mining-impacted sediments in the Cheyenne River watershed, South Dakota, USA - DeVore, Cherie L. (Environ Sci Process Impacts, 2019)
The mobilization of arsenic (As) from riverbank sediments affected by the gold mining legacy in north-central South Dakota was examined using aqueous speciation chemistry, spectroscopy, and diffraction analyses. Gold mining resulted in the discharge of approximately 109 metric tons of mine waste into Whitewood Creek (WW) near the Homestake Mine and Cheyenne River at Deal Ranch (DR), 241 km downstream. The highest concentrations of acid-extractable As measured from solid samples was 2020 mg kg(−1) at WW and 385 mg kg(−1) at DR. Similar sediment mineralogy between WW and DR was identified using XRD, with the predominance of alumino-silicate and iron-bearing minerals. Alkalinity measured in surface water at both sites ranged from 1000 to 2450 mg L(−1) as CaCO(3) (10–20 mM HCO(3)(−) at pH 7). Batch laboratory experiments were conducted under oxidizing conditions to evaluate the effects of NaHCO(3) (0.2 mM and 20 mM) and NaH(2)PO(3)(0.1 and 10 mM) on the mobilization of As. These ions are relevant for the site due to the alkaline nature of the river and nutrient mobilization from the ranch. The range of As(V) release with the NaHCO(3) treatment was 17–240 μg L(−1). However, the highest release (6234 μg L(−1)) occurred with 10 mM NaH(2)PO(3), suggesting that As release is favored by competitive ion displacement with PO(4)(3−) compared to HCO(3)(−). Although higher total As was detected in WW solids, the As(V) present in DR solids was labile when reacted with NaHCO(3) and NaH(2)PO(3), which is a relevant finding for communities living close to the river bank. The results from this study aid in a better understanding of As mobility in surface water sites affected by the mining legacy.